Sinyal Elektrik untuk Memperkaya Pengendalian Robot Jarak Jauh - Daniel Sutopo Pamungkas (Universitas Syiah Kuala, 2017)
A remote control operator enables a robot to perform in a hazard or area which can not be reached by humans. To control the robot, several researchers have equipped a robot with a system which can give others types of feedback information, besides of visual feedback from the robot. One of the feedback types is haptic feedback. The aim of this feedback is to make the operator become immersed with the robot. The existing researchers are using electro-mechanics system. However, these systems are complex, bulky, and hence prevent a seamless embodiment between an operator’s body. The objective of this research is to develop a haptic feedback system combined with stereo vision feedback which compact, versatile and easy to fit. This system is tested to accomplish the task using mobile robot and robot arm. The result shows that this system can help the operator to control robot better.